Existing knowledge on Euphorbia fischeriana Steud. (Euphorbiaceae): Traditional uses, clinical applications, phytochemistry, pharmacology and toxicology. (15th July 2021) - Li, Ya-Nan; He, Jun; Zhang, Jia; Shi, Ying-Xue; Guo, Lin-Bo; Peng, Zhong-Can; Yang, Ting; Ding, Kang; Zhang, Wei-Ku; Xu, Jie-Kun
Abstract: Ethnopharmacological relevance: Euphorbia fischeriana Steud. (Euphorbiaceae) is a perennial herb distributed in grassland, hill slopes or gravel hillside, with average altitude of 100–600 m. The whole grass of E. fischeriana is toxic with roots used as folk medicine to treat Zhushui, dyspepsia, abdominal distension, abdominal pain, cough, as well as external applications such as cure of scabies and tuberculosis of lymph nodes. Aim of the review: This systematic review aims to provide a detailed and in-depth summary about the reported advances in traditional uses, clinical applications, phytochemistry, pharmacology and toxicity of E. fischeriana, so as to offer fresh ideas and broader vision and insights for subsequent studies. Materials and methods: Various scientific data bases such as CNKI, Elsevier, Google Scholar, Pubmed, Science Direct, SciFinder Scholar and Web of Science were searched to collect information about E. fischeriana . Other relevant literatures were searched in 'Flora of China Editorial Committee', ancient books, Ph.D and Masters' Dissertation to get more data of E. fischeriana . Results: A total of 241 chemical constituents have been identified from the roots of E. fischeriana, including diterpenoids, triterpenoids, meroterpenoids, acetophenones, flavonoids, coumarins, steroids, phenolic acids, tannins, etc . Various pharmacological activities have been demonstrated, especially anti-tumor, antibacterial, anti-inflammatory, antiviral and anti-leukemia activities. Moreover, different investigations about clinical uses and toxicology of E. fischeriana indicated that attention should be paid to its usage and dosage. Conclusion: The researches of E. fischeriana are excellent, but gap still remains. As a poisonous traditional Chinese medicine, there are not enough studies on the toxicity of E. fischeriana . In addition, scholars' research on the pharmacological mechanism of E. fischeriana focuses more on the anti-tumor activity, which can be broadened in the future. Presumably, chemical constituents and biological activities of diterpenoids and trace meroterpenoids in E. fischeriana deserve further research in-depth in the future, in order to provide low toxicity and high efficiency lead compounds. Meanwhile, further studies on other medicinal aspects may lay a foundation for the comprehensive development and utilization of E. fischeriana . Graphical abstract: Image 1